Education Gamification and Student Motivation: A Case Study of Chinese Language Education - Chandra, Tasya; Deli, Deli (IJIE (Indonesian Journal of Informatics Education), 2023)
A new generation of pupils has grown up with a strong familiarity with technology in the context of Industry 4.0. This technological revolution has made learning a foreign language more critical. However, learning a foreign language can only be accessible with that crucial component- motivation. The purpose of this study was to find out how students' motivation to learn Mandarin was affected by gamification. A gamification application was designed with the Game Development Document (GDD) as a foundational guide, utilizing the Mechanics, Dynamics, and Aesthetics (MDA) architecture. Two schools participated in the experimental research project, with 56 and 58 students divided into control and experimental groups. A questionnaire gathered data, and SPSS was used to compute Cronbach's Alpha. The results showed that gamification increased students' enthusiasm to study Mandarin well. When employing gamification as a teaching strategy, students with different levels of Mandarin proficiency saw varied results. Therefore, gamification can tailor Mandarin language instruction to each student's needs and skill level.